2023
DOI: 10.21873/invivo.13064
|View full text |Cite
|
Sign up to set email alerts
|

Blueberry Leaf Extract Prevents Lacrimal Hyposecretion in Sjögren’s Syndrome-like Model of Non-obese Diabetic Mice

Abstract: Background/Aim: This study evaluated the effect of blueberry leaf hot water extract (BLEx) on Sjögren's syndrome (SS)-like lacrimal hyposecretion in male non-obese diabetic (NOD) mice. Materials and Methods: NOD or BALB/c mice were fed 1% BLEx or control (AIN-93G) for 2 weeks from the age of 4 to 6 weeks. Pilocarpine-induced tear volume was measured using a phenol red-impregnated thread. The lacrimal glands were evaluated histologically by H&E staining. The IL-1β and TNF-α levels in the lacrimal gland tissue w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…18,19 Tears are necessary to prevent dryness, shield the eye's surface from irritants, and feed the cells with oxygen and nutrients. 20 They are also necessary for the proper refraction of light to achieve clear vision. An abnormality of the ocular surface, such as dryness and lipid membrane disintegration, characterizes SS, a chronic, multifactorial eye disorder.…”
Section: Normal Anatomy and Function Of Lacrimal Glandmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 Tears are necessary to prevent dryness, shield the eye's surface from irritants, and feed the cells with oxygen and nutrients. 20 They are also necessary for the proper refraction of light to achieve clear vision. An abnormality of the ocular surface, such as dryness and lipid membrane disintegration, characterizes SS, a chronic, multifactorial eye disorder.…”
Section: Normal Anatomy and Function Of Lacrimal Glandmentioning
confidence: 99%
“…Tears include a variety of immunologically active proteins, peptides, and glycoproteins, which fight germs and keep tears from drying out 18,19 . Tears are necessary to prevent dryness, shield the eye's surface from irritants, and feed the cells with oxygen and nutrients 20 . They are also necessary for the proper refraction of light to achieve clear vision.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the above, work on finding effective, easily cultivated substitutes with proven effects, i.e., chokeberry, honeysuckle berry, seems to be highly advisable. Work on finding substitutes for bilberry fruit was carried out by Ogawa et al, where the authors investigated the possibility of using the more accessible leaves of this plant [22].…”
Section: Introductionmentioning
confidence: 99%
“…We reported the first evidence of the cytoprotective effect of BStEx against blue light-induced retinal cell damage in the field of eye health (16). In addition, we recently revealed that BLEx has a preventive effect on lacrimal hyposecretion (15).…”
mentioning
confidence: 96%
“…Additionally, it has been reported that BStEx contains proanthocyanidins with a relatively lower degree of polymerization than BLEx (14). Furthermore, BStEx and BLEx contain other phenolic compounds such as catechins, epicatechins, chlorogenic acid, quinic acid, and caffeic acid (15,16). Previous studies have shown that BStEx inhibits lipid synthesis in the liver (17), increases anti-adult T-cell leukemia (ATL) activity (18), and promotes viral proliferation (14).…”
mentioning
confidence: 99%